Does environmental regulation truly enhance corporate green environmental investment? Evidence from the supervision of independent directors in listed companies - Wang, Chao; Wang, Feifei; Jiang, Ping (Frontiers in Psychology, 2024)
Abstr act: With the increasingly prominent environmental issues in China, the government and citizens alike have intensified their focus on corporate investments in green environmental protection. Nevertheless, as government regulations become more stringent, there is substantial debate over whether environmental regulatory policies can consistently encourage listed companies to increase green environmental investments. Simultaneously, independent board supervision plays a crucial role in promoting the compliance and sustainability of listed companies regarding environmental protection. This paper selected a sample of 246 Chinese listed companies from 2010 to 2019, and used a fixed effects model to examine the impact 3,